2002
DOI: 10.1021/es0255251
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heterotrophic Microbial Growth on Biological Oxidation of Pyrite

Abstract: The rate and extent of pyrite oxidation by the iron-oxidizing bacteria Acidithiobacillus ferrooxidans was limited by the growth of the heterotrophic microbe Acidiphilium acidophilum. In batch systems containing a mixture of both organisms, the maximum zero-order rate of ferric iron accumulation was about 1.4 mg of Fe3+ L(-1) d(-1) as compared to 9.4 mg of Fe3+ L(-1) d(-1) for pure cultures of A. ferrooxidans under the same conditions. Pyrite oxidation was limited in cases where both cultures of organisms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Many previous researches (Peccia et al 2000;Marchand and Silverstein 2002; on the mix culture of these two species showed excess glucose or other organic compounds added to the mix culture medium enhanced the heterotrophic growth of Aph. acidophilum, while the organic compounds added to liquid medium and the metabolites derived from the growth of heterotrophic bacteria led to cellular toxin to autotrophic growth of At.…”
Section: Figmentioning
confidence: 93%
See 1 more Smart Citation
“…Many previous researches (Peccia et al 2000;Marchand and Silverstein 2002; on the mix culture of these two species showed excess glucose or other organic compounds added to the mix culture medium enhanced the heterotrophic growth of Aph. acidophilum, while the organic compounds added to liquid medium and the metabolites derived from the growth of heterotrophic bacteria led to cellular toxin to autotrophic growth of At.…”
Section: Figmentioning
confidence: 93%
“…On the one hand, previous researches on a mixed culture of these two strains showed that pure cultured At. ferrooxidans and its oxidation of ferrous iron and pyrite were inhibited by organic compounds (Marchand and Silverstein 2002;, while mix cultured with Aph. acidophilum permits to circumvent this inhibition.…”
Section: Introductionmentioning
confidence: 98%
“…Microorganisms can directly or indirectly utilize inorganic minerals as electron donors and irreversibly alter the physical conditions of the environments [33,34]. Pyrite (FeS 2 ) is the most abundant sulfide mineral on Earth and is an important player in the generation of mine drainage, as indicated by the following equations [6,35] …”
Section: Amd Generation and Associated Microorganismsmentioning
confidence: 99%
“…Owing to the increased concentration of Fe 3+ , the pyrite is sustainably dissolved, driving the primary production of mine drainage [21,34]. Thiosulfate, produced by pyrite oxidation at the original stage (with high ambient pH), can then also be oxidized by some bacteria and archaea (Equation (3)) [6].…”
Section: Amd Generation and Associated Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation